Functional domains of the RNA component of ribonuclease P revealed by chemical probing of mutant RNAs. - Shiraishi, H (1988)
The higher-order structure of the RNA component of ribonuclease P from Escherichia coli was analyzed using chemical probes. The secondary structure model which had been constructed from the comparative sequence analysis of the RNA was refined using the experimental data. In a mutant RNA (A89 RNA), which contains a G----A substitution at nucleotide 89, we detected a number of conformational alterations clustered between nucleotides 90 and 239. In view of the fact that A89 RNA is as catalytically active as wild-type RNA, but defective in association with the protein component, it is clear that the catalytic function of the RNA component resides on the structure which is not disrupted by the A89 mutation and that the structures altered by the mutation represent the region(s) interacting with the protein component. Another mutant (A329 RNA), which has a G----A substitution at nucleotide 329 and is defective in catalytic function, showed no detectable change in higher-order structure.